2021
DOI: 10.3390/ma14040890
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Biocomposites from Rapeseed Meal, Fruit Pomace and Microcrystalline Cellulose Made by Press Pressing: Mechanical and Physicochemical Characteristics

Abstract: This paper presents the results of research on biocomposites made of the mixture of post-extraction rapeseed meal, microcrystalline cellulose and various fruit pomace (chokeberry, blackcurrant, apple and raspberry pomace). The biocomposites were made in the process of mechanical thickening by means of a heated mould (die and stamp) which is located between two heating elements installed on a hydraulic press. The presented research combines mechanical engineering and material engineering issues. The physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Energy efficiency activities that can be undertaken by manufacturing companies and by different energy consumers in general can be divided into three categories. The first category includes optimization of the production processes, including using appropriate materials and devices and adjusting the machine settings and their performance to the actual needs [34]. The second category includes the prevention of energy losses caused by equipment failure or leakage of media distribution installations-for example, steam [14].…”
Section: Advanced Digital Production and Additive Manufacturing Technmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy efficiency activities that can be undertaken by manufacturing companies and by different energy consumers in general can be divided into three categories. The first category includes optimization of the production processes, including using appropriate materials and devices and adjusting the machine settings and their performance to the actual needs [34]. The second category includes the prevention of energy losses caused by equipment failure or leakage of media distribution installations-for example, steam [14].…”
Section: Advanced Digital Production and Additive Manufacturing Technmentioning
confidence: 99%
“…At the same time, along with the growing awareness of people about the negative impact of fossil fuel technology on the environment, any action to improve the surrounding environment is well perceived by the public. The use of entirely natural raw materials, consistent with the principles of sustainable development and "zero waste", is an important criterion in the production of modern products [34]. The new industrial age with paradigm of Industry 4.0 [91] offers the opportunity to deal with these variables simultaneously.…”
Section: The Clean Energy Package As An Increase In Energy Efficiencymentioning
confidence: 99%
“…In the same way, regarding the waste generated by the agro-industry, the composting technology has been sophisticated, evaluating the physicochemical characteristics of different raw materials, such as food waste or vegetable matter (fruits, wheat, cellulose). Through this technological development, the circular economy strategy for organic waste is promoted, not only in the use of waste, but also in the use that is given to composting by farmers [13]. However, the situation in emerging and developing economies is very different.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 6a of the cross-section of bamboo fiber, the inner tissue structure was preserved in the bamboo fiber with no resin entering into the cell cavity of the parenchyma, and the resin in the two sides of the fiber cured into the pores with a diameter of about 100 µm. It can be observed that a fiber was capsulated by the polymer matrix, fibers were pulled out, surface fibers were torn, and inner fibers were extracted, which was also stated in Reference [21]. Therefore, other than only tensile force in the TBF preparation, other factors should also be taken into consideration, including reducing the diameter, improving the specific surface area of TBF, and increasing the surface interaction between fiber and resin.…”
Section: Mechanical Performancementioning
confidence: 91%